2017
DOI: 10.1037/pne0000087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music therapy on the developing central nervous system of rats.

Abstract: This research was conducted to investigate the influence of music therapy on the behavior of rats at different stages of development. The procedures were performed when animals were approximately 1 month of age, and repeated once they completed 2, 3, and 4 months. Mozart's Sonata for Two Pianos was played at a sound intensity of 65 dB for 4 hours per day, 2 hours in the morning and 2 hours in the afternoon (12 hours, for 4 days) when the animals reached each age. In the Open Field test, the locomotion in rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a study, sub-chronic exposure (100 Db; 4h/day for 15 days) to noise produced increase in immobility time indicating a depression like behavior in rats 19 . However, there are also previous studies showing that music can ameliorate depression-like behavior in experimental animal 20 . On the other hand, they observed that depressive behavior had opposite levels at the juvenile age and at the adult age 20 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study, sub-chronic exposure (100 Db; 4h/day for 15 days) to noise produced increase in immobility time indicating a depression like behavior in rats 19 . However, there are also previous studies showing that music can ameliorate depression-like behavior in experimental animal 20 . On the other hand, they observed that depressive behavior had opposite levels at the juvenile age and at the adult age 20 .…”
Section: Discussionmentioning
confidence: 96%
“…However, there are also previous studies showing that music can ameliorate depression-like behavior in experimental animal 20 . On the other hand, they observed that depressive behavior had opposite levels at the juvenile age and at the adult age 20 . In addition, most of the studies which investigated the effects of classical music showed an amelioration on the structure of brain cells and neurochemistry following an improved behavior like enhanced spatial memory or decreased anxiety.…”
Section: Discussionmentioning
confidence: 96%
“…Relevant studies have shown that music has a positive impact on the mental and physical health of silver-haired people ( Vinciguerra, 2017 ). Therefore, it is a major direction of music research to improve the physical and mental health of silver-haired people by making them contact with music ( Sampaio et al, 2017 ). However, with increasing age, the physiological function and physical quality of the silver-haired group gradually degenerated, and most of the silver-haired group did not want to move.…”
Section: Introductionmentioning
confidence: 99%